2018
DOI: 10.1016/j.stemcr.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Status of KRAS in iPSCs Impacts upon Self-Renewal and Differentiation Propensity

Abstract: SummaryOncogenic KRAS mutations in hematopoietic stem cells cause RAS-associated autoimmune lymphoproliferative syndrome-like disease (RALD). KRAS plays essential roles in stemness maintenance in some types of stem cells. However, its roles in pluripotent stem cells (PSCs) are poorly understood. Here, we investigated the roles of KRAS on stemness in the context of induced PSCs (iPSCs). We used KRAS mutant (G13C/WT) and wild-type isogenic (WT/WT) iPSCs from the same RALD patients, as well as wild-type (WTed/WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Additionally, these pathways are also extensively reported in other processes such as immunosurveillance 157 , stem cell self-renewal 158 and epithelial to mesenchymal transition 159 . Some of these processes have already been described in endometriosis pathogenesis and they include Kras signalling 160,161 , MYC targets 162,163 , mTORC1 signalling [164][165][166] , PI3K AKT mTOR signalling [167][168][169][170] , TGF beta signalling [171][172][173] , interferon gamma [174][175][176][177] , and interferon alpha response 178,179 . In accordance with our data regarding microenvironment heterogeneity, certain pathways that are enriched in the stage III-IV phenotype are directly associated to M1-M2 macrophage polarization, and these pathways include TGF beta sinalling 180,181 , PI3K AKT mTOR signalling 151,182 , interferon gamma response 79 , adipogenesis, glycolysis and other metabolic reprograming pathways 183 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these pathways are also extensively reported in other processes such as immunosurveillance 157 , stem cell self-renewal 158 and epithelial to mesenchymal transition 159 . Some of these processes have already been described in endometriosis pathogenesis and they include Kras signalling 160,161 , MYC targets 162,163 , mTORC1 signalling [164][165][166] , PI3K AKT mTOR signalling [167][168][169][170] , TGF beta signalling [171][172][173] , interferon gamma [174][175][176][177] , and interferon alpha response 178,179 . In accordance with our data regarding microenvironment heterogeneity, certain pathways that are enriched in the stage III-IV phenotype are directly associated to M1-M2 macrophage polarization, and these pathways include TGF beta sinalling 180,181 , PI3K AKT mTOR signalling 151,182 , interferon gamma response 79 , adipogenesis, glycolysis and other metabolic reprograming pathways 183 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike to NF1 , PTPN11 , and HRAS , function of KRAS have not been well studied in the neurodevelopment. Kubara et al (2018) has been shown that activation of KRAS is required for self-renewal of iPSC. In their study, KRAS activation by p.G13C heterozygote mutation suppresses neuronal differentiation suggesting its role during the neurodevelopment.…”
Section: Kras Braf Mek1 Mek2 and Cardio-facio-cutaneous Smentioning
confidence: 99%
“…Cell lines in the second, smaller cluster, show high expression of genes related to KRAS activation (Bonferroni p=0.005; gene cluster 4 in Fig. 1B), which is associated with increased self-renewal of undifferentiated iPSCs and decreased neuronal differentiation propensity (14). Other gene clusters illuminate broad changes in gene expression over time such as a transient rise in MYC and E2F target genes in the early days of differentiation (gene cluster 13 in Fig.…”
mentioning
confidence: 99%